2013
DOI: 10.3390/molecules18032598
|View full text |Cite
|
Sign up to set email alerts
|

Ulososides and Urabosides — Triterpenoid Saponins from the Caribbean Marine Sponge Ectyoplasia ferox

Abstract: Three new triterpene glycosides, named ulososide F (1), urabosides A (2) and B (3), together with the previously reported ulososide A (4), were isolated from the Caribbean marine sponge Ectyoplasia ferox. Their structures were elucidated using extensive interpretation of 1D and 2D-NMR data, as well as HRESIMS. The aglycon of all compounds is a rare 30-norlonastane and the sugar residues were identified after acid hydrolysis and GC analyses. Cytotoxicities of the isolated compounds were evaluated against Jurkat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
2
15
0
1
Order By: Relevance
“…This approach for molecular structure identification using fragmentation patterns derived from MS 2 and MS 3 measurements indicated that the detected ions at m / z 851 ( 2 ), 716 ( 6 ) and 849 ( 18 ) are consistent with ulososide A, uloloside D and uraboside B, respectively (Figure 4), in comparison with previous reports for these compounds [10,19,20]. The precursor ion at m / z 851 was detected at three different retention times (45.1, 46.4 and 48.0 min), however, the identification of ulososide A as the peak at 46.4 min, did not represent a problem due to its fragmentation pattern (Figure 4A).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This approach for molecular structure identification using fragmentation patterns derived from MS 2 and MS 3 measurements indicated that the detected ions at m / z 851 ( 2 ), 716 ( 6 ) and 849 ( 18 ) are consistent with ulososide A, uloloside D and uraboside B, respectively (Figure 4), in comparison with previous reports for these compounds [10,19,20]. The precursor ion at m / z 851 was detected at three different retention times (45.1, 46.4 and 48.0 min), however, the identification of ulososide A as the peak at 46.4 min, did not represent a problem due to its fragmentation pattern (Figure 4A).…”
Section: Resultssupporting
confidence: 83%
“…[17], described four different saponins for E. ferox such as: Ectyoplaside A ([M + Na] + : m / z 953), Ectyoplaside B ([M + Na] + : m / z 969), Feroxoside A ([M + Na] + : m / z 1099) and Feroxoside B ([M + Na] + : m / z 1101). Those authors described the molecular structures of these saponins; however, it was also possible to determine in a previous report strong structural differences between triterpenoid skeletons of saponins from the Colombian sponge compared to that initially discovered from the Bahamas [10]. The saponins reported were: ulososide A ([M + Na] + : m / z 851), ulososide F ([M + Na] + : m / z 892), uraboside A ([M + Na] + : m / z 953) and uraboside B ([M + Na] + : m / z 849).…”
Section: Resultsmentioning
confidence: 99%
“…749,750 Finally, ulososide F 795, urabosides A 796 and B 797 are triterpene saponins from Ectyoplasia ferox (Caribbean Sea, Colombia), with 797 being the rst reported compound with both C-4 methyls elevated to the carboxylic acid oxidation state. 751…”
Section: Spongesmentioning
confidence: 99%
“…; Nephthea chabrolii (Wang et al 2012; Triterpenoid terdeteksi pada ekstrak etil asetet, n-heksana dan metanol pada kulit dan aksial ekstrak akar bahar. Penelitian Chung et al (2013;2014) menyatakan bahwa pada Rumphella antipathies dari campuran pelarut methanol dan diklorometan juga menemukan senyawa triterpenoid dari golongan seskuiterpenoid yaitu rumphellclovanes C-E dari dan 4,5-seco-caryophyllane yaitu rumphellaones B dan C. Colorado et al (2013) juga melaporkan mengisolasi tiga senyawa baru triterpen glikosida dari sponge Ectyoplasia ferox menggunakan pelarut methanol dan diklorometana.…”
Section: Radiumunclassified